Delta-like canonical notch ligand 1 in patients following liver transplantation: a secondary analysis of a prospective cohort study - Decker, Sebastian; Hildebrand, Dagmar; Bruckner, Thomas; Lichtenstern, Christoph; Heeg, Klaus; Weigand, Markus A.; Brenner, Thorsten; Uhle, Florian (Diagnostics, 2020)
Opportunistic bacterial infections are dreaded risks in patients following liver transplantation (LTX), even though patients receive an antibiotic prophylaxis. The timely recognition of such an infection may be delayed, as culture-based diagnostic methods are linked with a relevant gap in performance. We measured plasma concentrations of Delta-like canonical Notch ligand 1 (DLL1) in 93 adult patients at seven consecutive time points after liver transplantation and correlated the results to the occurrence of culture-proven bacterial infection or a complicated clinical course (composite endpoint of two or more complications: graft rejection or failure, acute kidney failure, acute lung injury, or 90-day mortality). Patients exhibited elevated plasma concentrations after liver transplantation over the whole 28 d observation time. Patients with bacterial infection showed increased DLL1 levels compared to patients without infection. Persistent elevated levels of DLL1 on day 7 and afterward following LTX were able to indicate patients at risk for a complicated course. Plasma levels of DLL1 following LTX may be useful to support an earlier detection of bacterial infections in combination with C-reactive protein (CRP) and procalcitonin (PCT), or they may lead to risk stratification of patients as a single marker for post-operative complications. (Clinical Trial Notation. German Clinical Trials Register: DRKS00005480).
Gesehen am 15.01.2020